The protocadherins, PCDHB1 and PCDH7, are regulated by MeCP2 in neuronal cells and brain tissues: implication for pathogenesis of Rett syndrome - Nakagawa Takayuki; Kudo Shinichi; Takahashi Kenichiro; Endoh Kazushi; Goto Yu-ichi; Itoh Masayuki; Soutome Masaki; Hirasawa Takae; Miyake Kunio; Yokoi Sana; Taira Takahiro; Inazawa Johji; et al. (BMC Neuroscience, 2011)
Abstract Background Rett syndrome is a neurodevelopmental and autistic disease caused by mutations of Methyl-CpG-binding protein 2 (MECP2) gene. MeCP2 protein is mainly expressed in neurons and binds to methylated gene promoters to suppress their expression, indicating that Rett syndrome is caused by the deregulation of target genes in neurons. However, it is likely that there are more unidentified neuronal MeCP2-targets associated with the neurological features of RTT. Results Using a genome-microarray approach, we found 22 genomic regions that contain sites potentially regulated by MeCP2 based on the features of MeCP2 binding, DNA methylation, and repressive histone modification in human cell lines. Within these regions, Chromatin immunoprecipitation (ChIP) analysis revealed that MeCP2 binds to the upstream regions of the protocadherin genes PCDHB1 and PCDH7 in human neuroblastoma SH-SY5Y cells. PCDHB1 and PCDH7 promoter activities were down-regulated by MeCP2, but not by MBD-deleted MeCP2. These gene expression were up-regulated following MeCP2 reduction with siRNA in SH-SY5Y cells and in the brains of Mecp2-null mice. Furthermore, PCDHB1 was up-regulated in postmortem brains from Rett syndrome patients. Conclusions We identified MeCP2 target genes that encode neuronal adhesion molecules using ChIP-on-BAC array approach. Since these protocadherin genes are generally essential for brain development, aberrant regulation of these molecules may contribute to the pathogenesis of the neurological features observed in Rett syndrome.